Governos militares e governo Alfonsín, 1976 1989: uma análise da política econômica argentina - Chayo, Marina Andrea de Hoffmann de (2010)
This work will study the 1976-1989 period with the aim to understand why Argentina is in this chaotic path since the lost decade . We will focus on Alfonsín constitutional government and take a look at the previous military administrations, from General Videla to General Bignone that left behind a complicated future for the nation, a huge public debt and a non-productive economy